P02 "It's just a little bit of add-on to the end, you know" Integrating joint pain, anxiety and depression in primary care long-term condition reviews: analysis of audio-recorded consultations. (13th September 2016) - Jinks, C; Liddle, J; Healey, EL; Mallen, CD; Chew-Graham, CA
Abstract : Background: Osteoarthritis (OA) and mental health problems are common and often co-exist in patients with other long term conditions (LTCs), but are under-detected and sub-optimally managed in primary care. The aim of the ENHANCE pilot trial is to develop and test the feasibility and acceptability of a practice nurse-led 'enhanced' LTC review for identifying, assessing and supporting management of identified joint pain, anxiety and/or depression in patients attending routine LTC reviews. We report analysis of audio recorded ENHANCE consultations undertaken as part of a process evaluation within the pilot trial. Methods: Practice nurses (PNs) at four general practices participated in training to deliver the ENHANCE review. A computer template prompted the use of case-finding questions for joint pain and anxiety and depression in the consultation. PNs had the option of verbal advice, referral to relevant services (e.g. physiotherapy and mental health services) and/or provision of information booklets. 24 consultations, with 7 PNs across the four practices were audio-recorded, transcribed and subject to a thematic analysis. The ENHANCE trial received NHS ethical approval. Results: ENHANCE LTC review recordings ranged between 10 and 50 minutes. Evidence of integration of ENHANCE components varied. Reference to the research study was given by some PNs as justification for departure from the usual LTC consultation. PNs and patients often normalised symptoms of low mood, anxiety and pain, there were missed opportunities to respond to patient cues, and sometimes help or resources were offered but not given. However, there were examples of highly integrated consultations where PNs did incorporate ENHANCE case-finding questions within a patient-centred discourse and offer further management. Pain management for OA was discussed, and topical agents were promoted particularly when patients expressed reluctance towards taking tablets. The importance of exercise was emphasised, and nurses handed out information booklets and talked patients through particular exercises. Information booklets for anxiety and depression were given and some patients were referred to their GP, but referral for formal support for mental health problems was not discussed. Conclusion: The complexity of the LTC review poses a challenge for integrating identification and assessment of OA, anxiety and/or depression within these consultations, and provision of support to patients with these problems. Despite the challenges, evidence that PNs can deliver an integrated approach indicates feasibility of the ENHANCE consultation within routine primary care. Facilitators to that integration will be discussed.